PERAN BRAND DISTINCTIVENESS DAN HALO EFFECT SEBAGAI MEDIASI PADA AESTHETIC VALUE, INFORMATION VALUE, DAN SELF-EXPRESSIVE VALUE TERHADAP PURCHASE INTENTION - Putri Sevrina Fazrin (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
The purpose of this research is to examine the influence of consumer value consisting of aesthetic value, information value, and self-expressive value on purchase intention through brand distinctiveness and the halo effect which act as mediating/intervening variables. The research object used in this research is Madame Gie Cosmetics products. This research uses a questionnaire as a self-administered survey. The scale used in this research is a 1-10 Likert scale. The sampling method used in this research was purposive sampling, which was distributed to 260 respondents. This research uses SEM (Structural Equation Modeling) with AMOS 22 software. The results of this research show that aesthetic value, information value, and self-expressive value influence brand distinctiveness and halo effect, which then influences brand distinctiveness and halo effect on purchase intention.